PENGARUH EKSPOR NETO, KURS DOLLAR AMERIKA SERIKAT, PRODUK DOMESTIK BRUTO DAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA INDONESIA TAHUN 1997-2016 - Yessi Ardianti, Dewa Ayu Made; Swara, Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Trade activity is defined as a process of exchange, arises because both countries see the advantages and benefits . It’s require important of payment that is foreign exchange reserves. This study aims to determine the effect of partial and then simultaneously between net export, US dollar, gdp , foreign debt to Indonesia's foreign exchange reserves. Another goal is to know the variables that have the most dominant influence on Indonesia's foreign exchange reserves. M ultiple linear regression is used for analytical , and use secondary data period 1996-2016. Based on the test results, simultaneously net exports, U S dollar, gdp and foreign debt significantly influence Indonesia's foreign exchange reserves period 1997-2016. Partially, foreign debt has a significant and positive influenc . Gdp, net exports, foreign debt, US dollar exchange rate hasn’t affected on foreign exchange reserves of Indonesia for analytical period of 1997-2016. The most dominant variable affecting foreign exchange reserves is foreign debt.